Performance Evaluation of Modulation and Power Allocation Effects on BER in NOMA with SIC over AWGN Channels - Defina Apriliani; Sopian Soim; Sholihin Sholihin (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2026)
This study evaluates the performance of a Non-Orthogonal Multiple Access (NOMA) system implementing Successive Interference Cancellation (SIC) over Additive White Gaussian Noise (AWGN) channels, focusing on the effects of modulation schemes and power allocation on Bit Error Rate (BER). Three modulation schemes BPSK, QPSK, and 16QAM are studied in combination with different power allocation configurations (e.g., α = 0.1, 0.3) for two users in an OFDM-based NOMA downlink scenario. The signal superposition process is performed at the transmitter side, while SIC is applied at the receiver side to separate the user signals. The simulation results show that the BER performance is greatly affected by the modulation level and power allocation ratio. Lower-order modulations (such as BPSK and QPSK) provide better performance at low SNR, especially for users with poorer channel quality. On the other hand, improper power distribution can cause error propagation in the SIC process, degrading the demodulation accuracy. This study emphasizes the importance of selecting adaptive modulation schemes and power allocation strategies in NOMA system design. These findings provide important contributions to the development of future wireless communication systems, especially 5G and later generations, which demand high spectral efficiency and multi-user service reliability.